MANAJEMEN SARANA PRASARANA KOMPLEKS STADION JALAK HARUPAT - Dadi Ginanjar Patradilaga; Yudha Munahat; Nuryadi Nuryadi (UNIVERSITAS NEGERI MAKASSAR, 2020)
The research objective was to see the Management of Infrastructure for the Jalak Harupat Stadium Complex. The research subject is the Youth and Sports Agency (BPO). Officials of Dispora, and administrators of UPTD of the Jalak Harupat stadium complex in Bandung Regency, which represent 6 people, 3 administrators of Dispora and 3 administrators of UPTD. The data technique uses the method of observation, interviews, and documentation. The analysis technique uses the Miles and Huberman model, which is called an interactive data analysis technique where data analysis is carried out interactively and continuously until it is complete, so that the data is saturated. The research results are as follows; 1) the development of the Jalak Harupat stadium complex has not been running optimally 2) the Jalak Harupat stadium complex requires a maintenance budget 3) the mobility of supervision in the Jalak Harupat stadium complex is constrained. Based on the various existing problems, the role of the management of youth sports bodies and administrators of the UPTD of the Starling Harupat stadium is very much needed in solving this problem of infrastructure management.